Efectos de la pandemia del COVID 19 en la dinámica familiar de las adolescentes de la I.E. Nº 35, Distrito de Guadalupe – 2020 - Miranda Salas, Stephanie Salome Nayari (2022)
The research entitled: "Effects of the COVID - 19 pandemic on the family dynamics of adolescents of the I.E N ° 35, District of Guadalupe - 2020, is a descriptive quantitative study that aims to analyze the effects of the pandemic in family dynamics. For which a total of 71 parents of the adolescents of the 1st grade of the I.E. For the investigation, the following methods were used: analytical - synthetic, inductive - deductive and statistical. The techniques used were: the survey, the interview and the review of documentary sources. The results obtained show that the pandemic significantly affected the dynamics of families. 48% of parents acknowledge that the pandemic affected the family environment. In the economic aspect, 73% of parents state that their income was less than 350 soles during the pandemic. The effect of COVID-19 on health was devastating, given the progression and generalization of the coronavirus, there were high rates of infection, 42% of parents claim to have been infected by the virus. On the other hand, the level of cohesion is characterized by 45% by separated families and the level of adaptability is characterized by 45% by chaotic families. Its operation is mid-range, presenting difficulties in only one dimension (adaptability). Finally, there was conditioning in the families, generated by the impact of COVID-19. What caused significant changes in families that consequently had to adapt in order to cope with the pandemic.